Accelerated Idioventricular Rhythm During Ajmaline Test: a Case Report - Sorgente, Antonio (Indian Heart Rhythm Society, 2010)
We present an unusual transient pro-arrhythmic effect of ajmaline in a patient with resuscitated cardiac arrest and a left ventricular apical aneurysm. We discuss the clinical presentation and the possible physio-pathological explanation for this new pro-arrhythmic effect linked to administration of intravenous ajmaline.